Complete nucleotide sequence of the gene for human interleukin 1 alpha. - Furutani, Y (1986)
The chromosomal gene for human interleukin 1 alpha (IL-1 alpha) was isolated from a human genomic DNA library by using as a probe cloned human IL-1 alpha cDNA. Complete nucleotide sequence of about 12 kilobase pairs (kbp) long was determined and the structure and organization of this gene were elucidated. This gene contains seven exons and six introns. The first exon encodes the 5'-untranslated region. Most of the prepeptide portion of the precursor polypeptide is encoded by the next three exons, and the mature form of IL-1 alpha is encoded by the remaining three exons. The last exon also encodes the intronless 3'-untranslated region. The fourth intron as well as both 5'- and 3'-flanking regions contains the sequence of an Alu family member. In the middle part of the last intron, a 46-bp sequence with a unique structure is repeated five times in a head to tail manner. These repeats are flanked by the regions containing alternative purine and pyrimidine tracts. In the 5'-flanking region, immediately upstream of the putative TATA box, the 16-bp sequence highly homologous to the binding site of the adenovirus 2 major late promoter transcription factor is identified. The nucleotide sequence reported here showed only one nucleotide substitution in the 3'-untranslated exon in comparison with the nucleotide sequence of the cDNA from HL-60, a promyelocytic leukemia cell line, previously cloned and sequenced in our laboratories.